One Step at a Time: A Latent Transitional Analysis on Changes in Substance Use, Exposure to Violence, and HIV/AIDS Risk Behaviors among Female Offenders - Jones, Abenaa Acheampong (American journal of criminal justice, 2018)
The aim of this analysis is to identify latent subgroups of women based on substance use, exposure to violence, and risky sexual behaviors and quantify discrete stages of behavior change over time. Data comes from 317 women recruited from a Municipal Drug Court System in the Midwest. All participants were interviewed regarding their substance use and sexual behaviors, as well as their exposure to violence at baseline, a 4th-month follow-up, and an 8th-month follow-up. A latent transitional analysis (LTA), a longitudinal extension of a latent class analysis (LCA), was used to quantify discrete stages of behavior change. The results of our analyses revealed 4 distinct behavioral profiles in our sample: 1) women with high probabilities of risky sexual behaviors, exposure to violence, and crack/cocaine use, 2) women with a high probability of exposure to violence, and moderate sexual risk taking, 3) women characterized solely by a high probability of crack/cocaine use, 4) women with low probabilities of all factors. The proportion of women in latent statuses characterized by a high probability of crack/cocaine use did not substantially decrease over time. Women who experienced child sexual abuse, had a greater number of lifetime arrests, were older, and believed they had risky drug using behavior that needed changing at baseline were significantly more likely to be in higher-risk latent statuses. Targeted interventions tailored to crack/cocaine users, as well as a wide-spread need for trauma-informed interventions among females involved in the criminal justice system, are needed.